Designing therapeutic waiting areas: a new media framework for reducing stress in healthcare environments - Raja Raimie, Raja Eda Shabina; Sabran, Mohammad Kamal; Azraai, Nur Zaidi (Universiti Teknologi MARA, Perak, 2025)
Long waiting times in healthcare settings are correlated with increased patient anxiety and dissatisfaction. Prolonged wait time averaging is 40 minutes in primary care clinics. Despite improvements in healthcare design, the necessary furnishings to provide a relaxing and healing environment are still lacking in many waiting areas. This issue is addressed gap in this study through an exploration of the potential of interactive media, guided by Lev Manovich’s principles of new media, to transform waiting areas into spaces of relaxation and to enhance well-being and contribute to Sustainable Development Goal 3 (Good Health and Well-being). A novel framework is developed for the designing of interactive media installations that incorporate visual nature, natural sounds, and interactivity to enhance patient experiences and promote well-being by applying Lev Manovich’s new media principles of modularity, variability, automation, and transcoding to interactive media installations. A triangulated qualitative methodology is employed, wherein contextual relevance is explored through semi-structured interviews with healthcare professionals (n=3), professional experts in new media (n=5), and patients (n=30), supplemented by document analysis of existing waiting area designs. The findings emphasize the importance of integrating natural elements and interactivity into media designs to create personalized, engaging patient experiences. The transformative potential of interactive media is highlighted in reducing stress, improving patient satisfaction, and fostering therapeutic environments aligning with SDG 3’s objective of ensuring healthy lives and promoting well-being for all ages. Manovich’s principles are extended into healthcare design, bridging theory and practice, and a roadmap is offered for implementing innovative media designs in healthcare facilities. It is recommended that future research empirically test the framework, evaluate its long-term impacts, and explore scalability across diverse healthcare settings.